Management of orofacial granulomatosis: a case report - Feugueur Guillaume; Konstantinou Maria Polina; Croze Jocelyn; Laurencin Sara; Cousty Sarah (EDP Sciences, 2018)
Introduction: Orofacial granulomatosis is characterized by recurrent swelling affecting the lips, cheeks, and tongue. The rarity of this pathology and the lack of consensus in therapeutic management make the reporting of this clinical case relevant. Observation: A 48-year-old man consulted for labial and gingival orofacial granulomatosis. The treatment consisted of 40 mg/L injections of triamcinolone acetonide once weekly for 3 weeks. The symptoms improved after 1 week of treatment. Comments: The usual treatment for this condition targets the inflammation caused by the lesion. Corticosteroids (clobetasol, triamcinolone acetonide, prednisolone), monoclonal antibodies (infliximab, adalimumab), or TNF-α inhibitors are commonly used. Symptom recurrenceis frequently observed after treatment with corticosteroids. Biotherapies are often used as a second-line treatment. Conclusion: Orofacial granulomatosis symptoms are rare and difficult to diagnose due to its varying manifestations. Common treatments target one of the steps of the inflammatory response. The detection of specific cellular markers is a way to enable a more precise etiological diagnosis and allows for a more targeted therapy.